Cerebral and systemic hemodynamic effect of recurring seizures - Lorenzo Ferlini (Nature Portfolio, 2021)
Abstract The increase in neuronal activity induced by a single seizure is supported by a rise in the cerebral blood flow and tissue oxygenation, a mechanism called neurovascular coupling (NVC). Whether cerebral and systemic hemodynamics are able to match neuronal activity during recurring seizures is unclear, as data from rodent models are at odds with human studies. In order to clarify this issue, we used an invasive brain and systemic monitoring to study the effects of chemically induced non-convulsive seizures in sheep. Despite an increase in neuronal activity as seizures repeat (Spearman’s ρ coefficient 0.31, P < 0.001), ictal variations of cerebral blood flow remained stable while it progressively increased in the inter-ictal intervals (ρ = 0.06, P = 0.44 and ρ = 0.22; P = 0.008). We also observed a progressive reduction in the inter-ictal brain tissue oxygenation (ρ =  − 0.18; P = 0.04), suggesting that NVC was unable to compensate for the metabolic demand of these closely repeating seizures. At the systemic level, there was a progressive reduction in blood pressure and a progressive rise in cardiac output (ρ =  − 0.22; P = 0.01 and ρ = 0.22; P = 0.01, respectively), suggesting seizure-induced autonomic dysfunction.